Proteomic and metabolomic studies on chilling injury in peach and nectarine - Lurie, Susan (Frontiers in Plant Science, 2022)
Peaches and nectarines are temperate climate stone fruit, which should be stored at 0 °C to prevent ripening of these climacteric fruit. However, if stored for too long or if stored at a higher temperature (4 or 5°C) they develop chilling injury. Chilling injury damage includes; 1) dry, mealy, woolly (lack of juice) fruit, 2) hard-textured fruit with no juice (leatheriness), 3) flesh browning, 4) flesh bleeding or internal reddening (Lurie and Crisosto, 2005). There are genetic components to these disorders in that early season fruit are generally more resistant than late season fruit, and white fleshed fruit more susceptible to internal browning than yellow fleshed fruit. A recent review covered the recent research in genomic and transcriptomic studies (Lurie, 2021), and this review examines findings from proteomic and metabolomics studies. Proteomic studies found that the ethylene synthesis proteins are decreased in cold compromised fruit and this affects the processes initiated by ethylene including cell wall and volatile changes. Enzymes in metabolic pathways were both higher and lower in abundance in CI fruit an indication of inbalance in energy production. Stress proteins increased in both fruit with or without CI, but were higher in damaged fruit. Metabolomics showed the role of levels of sugars, sucrose, raffinose, galactinol, and glucose-6-phosphate in protection against chilling injury, along with other membrane stabilizers such as polyamines. Amino acid changes were inconsistent among the studies. Lipid species changes during storage could be correlated to sensitivity or resistance to CI, but more studies are needed. Lurie, S. (2021). Genomic and Transcriptomic Studies on Chilling Injury in Peach and Nectarine. Postharvest Biol. Tech. 174, 111444. doi: 10.1016/j.postharvbio.2020.111444 Lurie, S. and Crisosto, C.H. (2005). Chilling injury in peach and nectarine. Postharvest Biol. Technol. 37, 195-208. doi:10.1016/j.postharvbio.2005.04.012